Splatoon. Vol. 14 - Hinodeya, Sankichi (VIZ Media, LLC, 2022)
"It's the Final Splatfest, with Team Blue vs. Team Hivemind! Then, during a new Turf War, Goggles and his friends take on a mysterious group of Inklings who look strangely familiar ... Can Team Blue defeat the Shadows?"--